2009
DOI: 10.1007/s00228-009-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP2C19 and CYP2C9 genotypes on pharmacokinetic variability of valproic acid in Chinese epileptic patients: nonlinear mixed-effect modeling

Abstract: The CYP2C19 and CYP2C9 genotypes significantly influenced the PK variability of VPA, as quantified by NONMEM software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
3
41
0
3
Order By: Relevance
“…There are at least three routes of VPA metabolism in humans: glucuronidation and β-oxidation in the mitochondria (both considered to be major routes accounting for 50% and 40% of the dose, respectively), and CYP-, such as CYP2C9 and CYP2C19, mediated-oxidation in the liver (considered to be a minor route, accounting for ∼10% of the dose) [24]. Similar to previous published population PK models for VPA [34][36], in the present study, a one-compartment model adequately described the VPA concentrations (Figure S1). …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There are at least three routes of VPA metabolism in humans: glucuronidation and β-oxidation in the mitochondria (both considered to be major routes accounting for 50% and 40% of the dose, respectively), and CYP-, such as CYP2C9 and CYP2C19, mediated-oxidation in the liver (considered to be a minor route, accounting for ∼10% of the dose) [24]. Similar to previous published population PK models for VPA [34][36], in the present study, a one-compartment model adequately described the VPA concentrations (Figure S1). …”
Section: Discussionsupporting
confidence: 61%
“…However, two other studies demonstrated an association between the CYP2C9 or CYP2C19 genotype and the PK parameters of VPA. Jiang et al reported that the CYP2C9 and CYP2C19 genotypes significantly influenced the population PK parameters of VPA in Chinese patients with epilepsy [34]. Tan et al indicated that subjects who were CYP2C9*3 allele carriers had higher mean plasma VPA concentrations than the non-carriers [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent population pharmacokinetic study in 287 Chinese patients with epilepsy showed that CYP2C9 in combination with CYP2C19 genotypes significantly influenced the pharmacokinetic variability of valproic acid, as quantified by population pharmacokinetic analysis [120]. UGT2B7 also contributes to the glucuronidation of valproic acid [68,121].…”
Section: Effect Of Genetic Polymorphisms Of Drug-metabolizing Enzymentioning
confidence: 99%
“…However, similar results were not achieved in other studies [41]. In addition, while there have been studies demonstrating the impact of CYP2C9 and/or CYP2C19 polymorphisms on VPA pharmacokinetics [28,42], other studies claimed no association between the CYP2C9 genotypes and VPA plasma concentrations or incidence of seizure [29,43,44]. We suppose such discrepancy lies in the fact that VPA is metabolized by multiple UGTs and CYPs, and the disposition could be related to other factors such as sample size, race, and patient age.…”
Section: Discussionmentioning
confidence: 56%